2010
DOI: 10.1103/physrevb.81.205410
|View full text |Cite
|
Sign up to set email alerts
|

Interband and plasma excitations in single-walled carbon nanotubes and graphite in inelastic x-ray and electron scattering

Abstract: The dynamical structure factor S͑q , ͒ in graphite, freestanding thin-bundled single-walled carbon nanotubes and bulk aligned nanotubes is probed by means of inelastic x-ray and electron scattering. We utilize the equivalency and complementarity of the two techniques in our combined approach. Both independent methods may be joined seamlessly. The joint extended experimental access to the plasmon dispersion exposes vividly the transition from screened plasmons at low momenta to uniform interband transitions at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…They observed that these two plasmonic modes were redshifted in comparison to the corresponding modes in the bulk graphite [2][3][4], due to the reduction of macroscopic screening when going from graphite to graphene [5]. The early momentum-dependent theoretical and experimental measurements observed linear dispersion of this π plasmon in graphene [6][7][8][9], which differs from the Q 2 dispersion reported in graphite [2,3,5,10].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…They observed that these two plasmonic modes were redshifted in comparison to the corresponding modes in the bulk graphite [2][3][4], due to the reduction of macroscopic screening when going from graphite to graphene [5]. The early momentum-dependent theoretical and experimental measurements observed linear dispersion of this π plasmon in graphene [6][7][8][9], which differs from the Q 2 dispersion reported in graphite [2,3,5,10].…”
Section: Introductionmentioning
confidence: 94%
“…The spectrum S(Q,ω) = E 2 (Q,ω)D(Q,ω) (10) in the absence of screening (D = 1) will have maxima at the energies of π → π * and σ → σ * SP transitions, as in Fig. 2(a), with Q 2 dispersion coming from the shape of the π and σ bands.…”
Section: (E) and 2(f)]mentioning
confidence: 99%
“…The results are compared to and discussed in respect to earlier studies of the momentum dependent loss-function as probed by angle-resolved electron energy-loss spectroscopy (AR-EELS) on graphite [9,7]. The methodical differences to other's earlier studies [10][11][12] are that we present the full angle resolved dispersion relation after combining IXS and AR-EELS.…”
Section: Introductionmentioning
confidence: 88%
“…Fig. 3 we compare the as measured IXS spectra of bulk turbostratic graphite and the VA-SWNT [7] at various momentum transfers q. The nanowires are measured in reflection geometry where q is along their net-alignment and the graphite is measured in transmission with q in the basal plane.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation